2015
DOI: 10.1016/s0140-6736(15)00851-x
|View full text |Cite
|
Sign up to set email alerts
|

A primary care pedometer-based walking intervention with and without practice nurse support: PACE-UP cluster-randomised controlled trial

Abstract: Background WHO guidelines recommend walking to increase moderate-to-vigorous physical activity. Pedometerbased interventions have focused on step-counts, not moderate-to-vigorous physical activity, and have not distinguished between pedometer and support eff ects. We assessed whether a postal pedometer-based walking intervention could increase step-counts and moderate-to-vigorous physical activity in inactive adults and whether physical activity consultations delivered by a practice nurse could add benefi t. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The complex interventions were well accepted by participants with 86% (129/150) attending all four nurse consultations in PACE-Lift and 74% (255/346) attending all three sessions in PACE-UP with the practice nurses delivering approximately 1400 PA consultations across the two trials. Both trials were successful and showed that the interventions were effective in increasing both average daily step-counts and time in moderate-to-vigorous physical activity at both 3 and 12 months, in 60–75 year olds in PACE-Lift [ 15 ] and 45–75 year olds in PACE-UP [ 16 ]. The trial protocols provide full details of each trial, the BCTs undertaken and procedures to ensure trial fidelity [ 17 , 18 ].…”
Section: Background To Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The complex interventions were well accepted by participants with 86% (129/150) attending all four nurse consultations in PACE-Lift and 74% (255/346) attending all three sessions in PACE-UP with the practice nurses delivering approximately 1400 PA consultations across the two trials. Both trials were successful and showed that the interventions were effective in increasing both average daily step-counts and time in moderate-to-vigorous physical activity at both 3 and 12 months, in 60–75 year olds in PACE-Lift [ 15 ] and 45–75 year olds in PACE-UP [ 16 ]. The trial protocols provide full details of each trial, the BCTs undertaken and procedures to ensure trial fidelity [ 17 , 18 ].…”
Section: Background To Studymentioning
confidence: 99%
“…Qualitative explorations from the perspectives of those delivering and receiving the intervention are recommended to provide a more in-depth understanding of complex interventions [ 24 , 25 ], enabling the intervention to be reproduced or adapted for the purposes of further research or for larger scale implementation [ 26 , 27 ]. To date we have reported the main results of both PACE-Lift and PACE-UP trials [ 15 , 16 ], the reasons for non-participation in both trials [ 28 , 29 ] and the views of intervention participants from the PACE-UP trial [ 30 ]. The aim of this paper is to provide an additional layer of evaluation by exploring the views of the practice nurses, focusing upon the perceived enablers and barriers to delivering the complex PA interventions, identifying the benefits they gained as practitioners from participating in the trial and their evaluation of the acceptability of the intervention for use within routine PA consultations in a GP setting.…”
Section: Background To Studymentioning
confidence: 99%
“…There is huge potential to use mobile phone apps and wearable devices that track patient physical activity to encourage further physical activity. The PACE-UP trial has successfully used pedometer and accelerometers with individual nurse support within general practice to increase patient physical activity 18 and the use of competitions such as the community physical activity challenges like Beat The Street are promising (https:// www.beatthestreet.me/UserPortal/Default).…”
Section: Initiatives To Increase Physical Activitymentioning
confidence: 99%